Signals Involved in Arabidopsis Resistance to Trichoplusia ni Caterpillars Induced by Virulent and Avirulent Strains of the Phytopathogen Pseudomonas syringae - Cui, Jianping (American Society of Plant Physiologists, 2002)
Plants have evolved different but interconnected strategies to defend themselves against herbivorous insects and microbial pathogens. We used an Arabidopsis/Pseudomonas syringae pathosystem to investigate the impact of pathogen-induced defense responses on cabbage looper (Trichoplusia ni) larval feeding. Arabidopsis mutants [npr1, pad4, eds5, and sid2(eds16)] or transgenic plants (nahG) that are more susceptible to microbial pathogens and are compromised in salicylic acid (SA)-dependent defense responses exhibited reduced levels of feeding by T. ni compared with wild-type plants. Consistent with these results, Arabidopsis mutants that are more resistant to microbial pathogens and have elevated levels of SA (cpr1 and cpr6) exhibited enhanced levels of T. ni feeding. These experiments suggested an inverse relationship between an active SA defense pathway and insect feeding. In contrast to these results, there was increased resistance to T. ni in wild-type Arabidopsis ecotype Columbia plants that were infected with P. syringae pv. maculicola strain ES4326 (Psm ES4326) expressing the avirulence genes avrRpt2 or avrB, which elicit a hypersensitive response, high levels of SA accumulation, and systemic acquired resistance to bacterial infection. Similar results were obtained with other ecotypes, including Landsberg erecta, Cape Verdi Islands, and Shakdara. When infected with Psm ES4326(avrRpt2) or Psm ES4326(avrB), nahG transgenic and npr1 mutant plants (which are more susceptible to virulent and avirulent P. syringae strains) failed to show the increased insect resistance exhibited by wild-type plants. It was surprising that wild-type plants, as well as nahG and npr1 plants, infected with Psm ES4326 not expressing avrRpt2 or avrB, which elicits disease, became more susceptible to T. ni. Our results suggest two potentially novel systemic signaling pathways: a systemic response elicited by HR that leads to enhanced T. ni resistance and overrides the SA-mediated increase in T. ni susceptibility, and a SA-independent systemic response induced by virulent pathogens that leads to enhanced susceptibility to T. ni.